Exercises in Synthetic Organic Chemistry. - Ghiron, Chiara (Oxford University Press, 1997)
Ideal as a basis for group discussions of organic chemistry this textbook is designed for both final year chemistry undergraduate and postgraduate organic chemistry students. Comprised of a series of exercises based around recently published syntheses, each exercise gives a reference to the original work, and a synthetic scheme in which either structures or reagents have been omitted. Also included are a series of written questions on the exercises, and in most cases some references to related literature and useful reviews. These exercises will provide challenges for people with various levels of experience from final year undergraduates to academic staff and industrial group leaders.; This book is intended for primary market: Final year chemistry undergraduate and postgraduate organic chemistry students; Secondary market: Industrial chemistry departments.